2017
DOI: 10.3389/fpls.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Effects on Seed and Seedling Phenotypes in Reciprocal F1 Hybrids of the Common Bean (Phaseolus vulgaris L.)

Abstract: Maternal control of seed size in the common bean provides an opportunity to study genotype-independent seed weight effects on early seedling growth and development. We set out to test the hypothesis that the early heterotrophic growth of bean seedlings is determined by both the relative amount of cotyledon storage reserves and the genotype of the seedling, provided the hybrid genotype could be fully expressed in the seedlings. The hypothesis was tested via comparison of seed weight and seedling growth phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 43 publications
(56 reference statements)
3
42
1
Order By: Relevance
“…PCA results could be biased because seed weight was the main target of selection during domestication, and we have shown that seed reserves can significantly influence early heterotrophic growth (Singh et al, 2017). Thus, seed weight differences between wild and domesticated accessions could explain some of the root growth differences between the accessions as suggested by the significant phenotypic correlations between seed weight and many root traits, and root size traits in particular ( Supplemental Tables S3 and S4).…”
Section: Comparative Root System Analysis Of Wild and Domesticated Acmentioning
confidence: 97%
See 2 more Smart Citations
“…PCA results could be biased because seed weight was the main target of selection during domestication, and we have shown that seed reserves can significantly influence early heterotrophic growth (Singh et al, 2017). Thus, seed weight differences between wild and domesticated accessions could explain some of the root growth differences between the accessions as suggested by the significant phenotypic correlations between seed weight and many root traits, and root size traits in particular ( Supplemental Tables S3 and S4).…”
Section: Comparative Root System Analysis Of Wild and Domesticated Acmentioning
confidence: 97%
“…A RIF with 186 genotypes (F 6:8 ) was generated from a cross between a landrace (G19833) from Northwestern Peru (6.27°S, 77.75°W) and a wild accession (G23419) from Central Peru (11.23°S, 75.53°W). The two genotypes exhibit significant phenotypic and gene expression differences at early seedling stage (Singh et al, 2017(Singh et al, , 2018. The intra-Andean wild-landrace RIF excluded traits that may be found in modern cultivars and those controlling intergenepool variation.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed and early seedling morphology and physiology is thought to be influenced by the genetic makeup and environment of the parent plant more so than the genotype of the embryo (González-Rodrígueza et al 2011;Singh et al 2017). This is partly through maternal effects that affect provisioning of resources to embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that a lot of work has been dedicated to studying the ecological and evolutionary consequences of hybridization in plants, much less attention has been paid to how maternal parents influence the phenotypes of their offspring (i.e. maternal effects) immediately after hybridization (Kimball et al 2008;Piskurewicz et al 2016;Singh et al 2017). The maternal effect, defined by Roach and Wulff (1987) as "the contribution of the maternal parent to the phenotype of its offspring beyond the equal chromosomal contribution expected from each parent", can be arbitrarily split into two groups: i) maternal environment effects, where phenotypic differences in the offspring are due to differential environmental conditions experienced by the maternal parents (Chiang et al 2011;Fernández Farnocchia et al 2019); and ii) maternal genetic effects, where phenotypic differences in the offspring are due to the maternal parent´s phenotype or genotype (Roach & Wulff 1987;Pace et al 2015;Singh et al 2017).…”
Section: Introductionmentioning
confidence: 99%